Upaya Memperbaiki Kebersihan Jalan Nafas Pada Pasien Pneumonia - Utomo, Rezky Putro, Arina Maliya, S.Kep., M.Si.Med (2017)
Introduction : Pneumonia is the leading cause of morbidity and mortality in adults, pneumonia is inflammation of the lung parenchyma caused by viruses, bacteria, mycoplasma which enters the body so that causes a decrease in the supply of O2 into the body that causes shortness of breath. Purpose of nursing care in patients with pneumonia ineffectiveness breathing pattern. According to data from the WHO and UNICEF are the main cause of bacterial pneumonia, 50% were Streptococcus pneumoniae (pneumococcal bacteria), 20% were caused by Haemophilus influenzaetype B (Hib), the rest are viral and other causes. Method : qualitative case study approach and perform nursing care in patients with pneumonia cleanliness airway in Cempaka Pavilion Hospital Jombang, which includes assessment, nursing diagnosis, planning, implementation, and evaluation. Results: of research at patients 1 and 2 pneumonia with the ineffectiveness of breathing patterns, evaluation on day 3 in get colie resolved problem results partly evidenced by keduan patients alike say tightness is reduced. Discussion : Hopefully this research can be used as a source or insight as well as the development of science and as a reference to add knowledge about nursing care in patients with pneumonia ineffectiveness breathing pattern Keywords: Pneumonia, Cleanliness airway.